Data from: Negative frequency-dependent foraging behaviour in a generalist herbivore (Alces alces) and its stabilizing influence on food-web dynamics ... - Hoy, Sarah R.; Vucetich, John A.; Liu, Rongsong; DeAngelis, Don L.; Peterson, Rolf O.; Vucetich, Leah M.; Henderson, John J. (Dryad, 2019)
1.Resource selection is widely appreciated to be context‐dependent and shaped by both biological and abiotic factors. However, few studies have empirically assessed the extent to which selective foraging behaviour is dynamic and varies in response to environmental conditions for free‐ranging animal populations. 2.Here, we assessed the extent that forage selection fluctuated in response to different environmental conditions for a free‐ranging herbivore, moose (Alces alces) in Isle Royale National Park, over a 10‐year period. More precisely, we assessed how moose selection for coniferous versus deciduous forage in winter varied between geographic regions and in relation to: (i) the relative frequency of forage types in the environment (e.g., frequency‐dependent foraging behaviour), (ii) moose abundance, (iii) predation rate (by gray wolves), and (iv) snow depth. These factors are potentially important for their influence on the energetics of foraging. We also built a series of food‐chain models to assess the ... : Data file for analysisThis file contains all of the data used in the empirical analysis of moose selection for conifer and balsam fir in Isle Royale National Parkisro.data.for.dryad.txt ...